The Absurdism in Guillermo Barquero's "La hora de las confesiones" and El extranjero by Albert Camus: a Comparative Study - Huertas Arredondo, Kimberly (2022)
The main objective of this article is to analyze the different features involved in the intertextual analogy between the tale “La hora de las confesiones” (2013) by the Costa Rican writer Guillermo Barquero and El extranjero (1942) by the writer Albert Camus, in which the philosophy of absurdism is presented. Particularly, this study focuses on the expressive features of the absurdism and its implications regarding the arrangement of the textual interweaving of the story. As theoretical and methodological referents, the philosophical essay El mito de Sísifo (1942) and the intertextuality theory by Julia Kristeva (1978) are going to be used. It was found that the text has an intertextual correspondence with the philosophy present in El extranjero by means of Kafka that uses techniques such as strangeness, as well as the creation of an absurd climate and the overcoming of the absurd through rebellion, freedom and passion. In the other hand, there are some divergences between the two authors.